Lessons Learned from the Holocaust and the Contemporary Genocide - Dokmanović, Mišo (Review of European and Comparative Law, 2023)
The paper is focused on the analysis of the lessons learned from the genocides in the 20th century for the existing situation in Ukraine. Apart from the short overview of the history behind the term genocide and the adoption of the convention for its prevention and punishment in the post-World War II period, the paper explores the main specifics of the selected genocides (Armenian genocide, the Holocaust, Cambodia, Rwanda, and Yugoslavia). On the basis of the identified specifics, several conclusions and lessons have been drawn, including the expectation that mass atrocities will happen again and that international justice is often slow and deals with a limited number of perpetrators.